THE POETICS OF THE IMAGE OF PETS IN EXPRESSING THE WORLD’S ARTISTIC LANDSCAPE (IN THE EXAMPLE OF MODERN UZBEK POETRY) - Urokova Nafosat Yoriyevna; Turayeva Laylo Omonovna; Normuratova Nigora Rustam qizi; Khayriyeva Nargiza Ikhtiyor kizi (Utilitas Mathematica, 2025)
The term “artistic landscape of the world” and studies of its theory are actual topics that are in the center of attention of world literary studies. Various linguopoetic means are used to express the artistic landscape of the world. The most active users of these are images, poetic movements and artistic arts. In particular, the role of faunistic images in this regard is incomparable.In literary studies, soke topics as the theory of poetry, the use of artistic figurative means, the symbol and its manifestations in lyrics, the symbolization of the animal and plant world, the foundations of its origin, and the disclosure of aspects specific to the poetics of poems on this topic are being actual. In particular, the manifestations of the symbol, the dominance of symbolization in poetry, the embodiment of animal images, and the elucidation of its specific features are of great importance. A number of research works related to animalistic literature have been carried out in world literary studies. In particular, the animal world has been studied in various aspects in the studies of K.Vijil, S.Belogurova, I.Lunina, and B.Mirsaidov1.